Secretary [videorecording (Blu-Ray)] - Wilson, Erin Cressida; Spader, James; Gyllenhaal, Maggie, 1977-; Fierberg, Steven; Badalamenti, Angelo; Gaitskill, Mary, 1954- (Lionsgate, 2010)
Lee has a few strikes against her when she applies for a secretarial position at the law office of E. Edward Grey. In between typing, filing and coffee making, Lee and Mr. Grey embark on a personal relationship together, crossing the line.